Position statement and updated international guideline for safe and effective whole-body electromyostimulation training-the need for common sense in WB-EMS application - Kemmler, Wolfgang; Fröhlich, Michael; Ludwig, Oliver; Eifler, Christoph; von Stengel, Simon; Willert, Sebastian; Teschler, Marc; Weissenfels, Anja; Kleinöder, Heinz; Micke, Florian; Wirtz, Nicolas; Zinner, Christoph; et al. (Frontiers in Physiology, 2023)
Whole-Body Electromyostimulation (WB-EMS) is a training technology that enables simultaneous stimulation of all the main muscle groups with a specific impulse intensity for each electrode. The corresponding time-efficiency and joint-friendliness of WB-EMS may be particularly attractive for people unable or unmotivated to conduct (intense) conventional training protocols. However, due to the enormous metabolic and musculoskeletal impact of WB-EMS, particular attention must be paid to the application of this technology. In the past, several scientific and newspaper articles reported severe adverse effects of WB-EMS. To increase the safety of commercial non-medical WB-EMS application, recommendations “for safe and effective whole-body electromyostimulation” were launched in 2016. However, new developments and trends require an update of these recommendations to incorporate more international expertise with demonstrated experience in the application of WB-EMS. The new version of these consensus-based recommendations has been structured into (i) “general aspects of WB-EMS”, (ii) “preparation for training”, recommendations for the (iii) “WB-EMS application” itself and (iv) “safety aspects during and after training”. Key topics particularly addressed are (1) consistent and close supervision of WB-EMS application, (2) mandatory qualification of WB-EMS trainers, (3) anamnesis and corresponding consideration of contraindications prior to WB-EMS, (4) the participant's proper preparation for the session, (5) careful preparation of the WB-EMS novice, (6) appropriate regeneration periods between WB-EMS sessions and (7) continuous interaction between trainer and participant at a close physical distance. In summary, we are convinced that the present guideline will contribute to greater safety and effectiveness in the area of non-medical commercial WB-EMS application.